Interaction of the autoimmune profile peculiarities in patients with cataract and pseudoexfoliation syndrome with the development of hydrodynamic disturbances - M. Z. Frankovska-Gerlak; S. A. Bozenok; P. E. Brizhak; A. U. Menshikov; G. V. Sorokoletov (Офтальмохирургия, 2016)
Pseudoexfoliation syndrome (PEX) is the established trigger of glaucoma. The systemic character of PEX and the multifactorcharacter of glaucoma can point to possible changes of the autoimmune profile of human body in the presence of this pathology and its possible link with hydrodynamic disturbances.Purpose. To study the peculiarities of the autoimmune serum profile in patients with cataract and PEX in the presence andabsence of glaucoma.Material and methods. In the study there were examined 45 female patients aged 70-84 years with cataract and severe PEX. The patients were divided into 3 groups depending on the intensity of systemic cardio-vascular pathology and the presence or absence of glaucoma. Enzyme-linked immunosorbent assay was used to define the serum autoantibody level.Results. In examined groups it was detected the exceeding of the average statistical norm of the following serum autoantibodies: to the cytoplasm of neutrophilic granulocytes (ANCA), β1-adrenoreceptors and membrane antigen of trombocyte, which was the most pronounced one in the presence of systemic cardiovascularpathology and glaucoma process.Conclusions. The detected peculiarities of the autoimmune activity in patients with PEX can point to the significant role of the endothelial dysfunction in the development of glaucoma in such group of patients.